Research methodology : methods and techniques - Kothari, C R; Garg, Gaurav (New Delhi : New age international, 2022)
This fourth multi color edition has been made better equipped to make the learning more systematic. More details are added to old chapters keeping in mind the need of advanced data analysis in social science research. The usage of popular statistical package SPSS has also been shown through many examples. It is important to adopt an appropriate methodology in quality research. The present book provides the basic and advanced level discussion on research methodology so that the researchers may become familiar with the art of using research methods and techniques. The book is intended to serve as a textbook for social science students at graduate and postgraduate level. The book can be taken as a well organized guide for researchers in social science and other areas..
Includes bibliographical references (p. 449-453) and index.
Keywords: Advanced data analysis in social science research; Statistical package for the social sciences (SPSS).; Research methodology for quality research; Advanced level discussion on research methodology; Researchers in social science